Intramuscular Hemangioma of the Forearm with Flexion Contracture - Niempoog, Sunyarn (Case Rep Orthop, 2019)
Intramuscular hemangiomas can be an infrequent but important cause of musculoskeletal pain. This report describes a 25-year-old male who presented with pain in the right forearm and contracture of the right hand for 4 years. Physical examination revealed severe tenderness of the midforearm with contracture of the flexor tendons in the index, middle, ring, and little fingers. Conventional radiography of the forearm revealed a soft tissue phlebolith. Magnetic resonance imaging showed a well-defined lobulated mass partially involving the FDP tendon. An intramuscular hemangioma within the deep anterior compartment of the forearm was suspected. Following surgical excision of the hemangioma, the patient's symptoms resolved completely. In conclusion, intramuscular hemangioma can be a rare cause of flexion contracture of the hands and should be considered as a cause of a flexion contracture that fails to respond to conservative treatment.